THE EFFECT OF LEARNING STRATEGY AND CRITICAL THINKING ON EXPOSITION WRITING ABILITY IN 6TH GRADE ELEMENTARY SCHOOL - Raden Bambang Nur’aryanto; Is Eka Herawati (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThis study aims to determine the effect of the use of problem-based learning, inquiry learning strategies, and critical thinking skills on exposition writing ability. The research method used is an experimental method, in two different study groups. The research design used was factorial design. Data grouping is distinguished through two treatments, namely learning strategies and critical thinking called factors or main effects and differences in each treatment called levels. Based on the results of the calculations, the research results obtained that: (1) There are differences in the ability to write expositions between students who study using problem-based learning strategies and inquiry strategies. (2) There are differences in the ability to write an exposition of students who have high critical thinking skills with students who have low critical thinking skills. (3) For students who have high critical thinking skills, the ability to write expositions is better using problem-based learning strategies than using inquiry strategies. (4) For students who have low critical thinking skills, the ability to write exposition is higher using an inquiry strategy than using a problem-based learning strategy. (5) There is an interaction effect between the use of problem-based learning strategies and students’ critical thinking on the ability to write expositions.Keywords: Problem Based Learning; Critical Thinking